PML Degradation: Multiple Ways to Eliminate PML - Rabellino, Andrea (Frontiers Media S.A., 2013)
The promyelocytic leukemia tumor suppressor gene (PML) critically regulates several cellular functions that oppose tumorigenesis such as oncogene-induced senescence, apoptosis, the response to DNA damage and to viral infections. PML deficiency occurs commonly in a broad spectrum of human cancers through mechanisms that involve its aberrant ubiquitination and degradation. Furthermore, several viruses encode viral proteins that promote viral replication through degradation of PML. These observations suggest that restoration of PML should lead to potent antitumor effects or antiviral responses. In this review we will summarize the mechanisms involved in PML degradation with the intent to highlight novel therapeutic strategies to trigger PML restoration.